UJI AKTIVITAS ANALGETIK EKSTRAK DAUN CINCAU HIJAU ATAU DAUN DALUMAN (CYCLEA BARBATA MIERS) PADA MENCITSEBAGAI TERAPI GASTRITIS - Burhanudin Gasim Soka (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2025)
Green Grass Jelly Leaf (Cyclea barbata Miers), commonly known in Indonesia as "Daun Daluman" or green cincau, is widely distributed throughout various regions in Indonesia, ranging from traditional markets to modern shopping centers. This plant is recognized for its medicinal potential, particularly in the treatment of gastritis. Its therapeutic effects are attributed to the presence of several bioactive compounds, including alkaloids, saponins, tannins, and flavonoids. Gastritis is a common condition characterized by inflammation of the gastric mucosal lining. It may result from various etiological factors such as Helicobacter pylori infection, prolonged use of non-steroidal anti-inflammatory drugs (NSAIDs), psychological stress, and unhealthy dietary habits. The aim of this study was to evaluate the analgesic activity of green grass jelly leaf extract (Cyclea barbata Miers) in mice induced with acetic acid and to assess the protective effects of the extract on the gastric mucosa. This research employed an experimental laboratory method using an in vivo approach with mice as test animals. The results of the analgesic test indicated that the group treated with the green grass jelly leaf infusion showed a significantly different mean number of writhing responses compared to the negative control group. Specifically, the negative control group exhibited an average of 84 writhes, whereas the positive control group showed 19.6 writhes. These findings suggest that the infusion of Cyclea barbata leaves possesses notable analgesic activity. The number of writhes observed in mice serves as an indicator of pain intensity in response to acetic acid-induced nociception. A lower number of writhes implies reduced pain perception, thereby reflecting a stronger analgesic effect.